Biochar Application and Mowing Independently and Interactively Influence Soil Enzyme Activity and Carbon Sequestration in Karst and Red Soils in Southern China - Wenjia Luo; Daniel F. Petticord; Shiwen Zhu; Shaowu Zhu; Yuanlong Wu; Xun Yi; Xinyue Wang; Yili Guo; Xuxin Song (Agronomy)
Soil organic carbon (SOC), a critical component of the global carbon cycle, represents the largest terrestrial carbon reservoir, and is thus a major component of influencing climate regulation and ecosystem health. Grasslands store substantial carbon in their soils, but this carbon reservoir is easily degraded by both grazing and mowing, particularly in vulnerable karst landscapes. This study investigates the potential of biochar, a carbon-rich soil amendment, as a management tool to maintain SOC or mitigate the degradation of SOC during mowing in karst grasslands in Southern China, using both red acidic and calcareous soils as experimental variables. T SOC fractions, soil enzyme activities, and soil pH were measured to determine the effect of mowing and biochar application on carbon stability and microbial activity. Consistent with expectations, mowing increases belowground biomass and promotes carbon loss through increased microbial activity, particularly in calcareous soils where mowing also decreases soil pH, increasing acidity and reducing the stability of Ca–carbon complexes. Biochar, however, counteracted these effects, increasing both particulate organic carbon (POC) and mineral-associated organic carbon (MAOC), especially in red soils where the addition of biochar greatly increased soil pH (from 5.4 to 6.33) (an effect not observed in the already-alkaline karst soils). Enzyme activities related to carbon degradation, such as β-D-Glucosidase and peroxidase, increased in biochar-amended soils (β-D-Glucosidase increased from 12.77 to 24.53 nmol/g/h and peroxidase increased from 1.1 to 2.36 mg/g/2h), each of which contribute to the degradation of carbon containing organic matter so that it may be ultimately stored in more recalcitrant forms. Mowing led to reduced polyphenol oxidase activity, but the presence of biochar mitigated these losses, protecting SOC pools (increased from 0.03 to 0.79 mg/g/2h). This study highlights biochar as an effective tool for enhancing SOC stability in karst grasslands, particularly in acidic soils, and suggests that integrating biochar into mowing regimes may optimize carbon sequestration while reducing fire risk. These findings offer valuable theoretical guidance for developing sustainable land management in sensitive ecosystems.